Organic chemistry on surfaces: Direct cyclopropanation by dihalocarbene addition to vinyl terminated self-assembled monolayers (SAMs) - Adamkiewicz, Malgorzata; O’Hagan, David; Hähner, Georg (Beilstein Journal of Organic Chemistry, 2014)
C11-Vinyl-terminated self-assembled monolayers (SAMs) on silica surfaces are successfully modified in C–C bond forming reactions with dihalocarbenes to generate SAMs, terminated with dihalo- (fluoro, chloro, bromo) cyclopropane motifs with about 30% surface coverage.
Keywords: difluoro-; dichloro-; dibromomethylenecyclopropanes; dihalocarbenes; self-assembled monolayers; surface coating